Resveratrol protects quail hepatocytes against heat stress: modulation of the Nrf2 transcription factor and heat shock proteins - Şahin, Kazım; Orhan, C.; Akdemir, F.; Tuzcu, M.; Iben, C.; Şahin, Nurhan. (Wiley, 2012)
In the present study, the effects of dietary resveratrol on the induction of heat shock proteins, transcription factors and antioxidative enzyme system in liver of quails under heat stress were investigated. A total of 180 (55-day-old) female Japanese quails (Coturnix coturnix japonica) were reared either at 22 degrees C for 24 h/day (thermoneutral, TN) or 34 degrees C for 8 h/day (heat stress, HS; 09:0017:00 hours) for 12 weeks. Birds in both environments were randomly fed one of three diets: basal diet and basal diet added with either 200 or 400 mg of resveratrol per kg of diet. The results showed that exposure to high ambient temperature induced decreases in feed intake, egg production, and hepatic superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) activities but increases in hepatic malondialdehyde (MDA) concentrations (p < 0.001). Liver Hsp70, Hsp90 and NF-?B expression was greater while Nrf2 expression was lower for quails reared under the heat stress than for those reared under the TN environment (p < 0.0001). There were linear increases in feed intake, egg production, hepatic SOD, CAT, and GSH-Px activities as well as Nrf2 expression, but linear decreases in hepatic MDA concentrations and Hsp70, Hsp90, and NF-B expressions with increasing supplemental resveratrol level (p < 0.0001). Two-way treatment interactions revealed that the degree of restorations in all response variables was more notable under the high ambient temperature than that of the TN environment as dietary resveratrol concentration was increased. The results of the present study suggest that supplemental resveratrol reduces oxidative stress in heat-stressed quails through modulating the hepatic heat shock proteins and nuclear transcription factors.
Keywords: resveratrol; heat shock proteins; Nrf2; NF-?B; heat stress; quail